Learning to lead: a discussion of development programs for academic leadership capability in Australian Universities. Issue 4 (3rd July 2020) - Butler, Jane
ABSTRACT: This paper critically explores the opportunity for leadership development in higher education within an interpretative inquiry paradigm from the perspective of middle-level academics transitioning into leadership/management roles in Australian universities. Middle-level academics are described as being at a mid-point in their careers and universally appear to represent a substantial percentage of academic personnel in tertiary institutions. Much has been written about the rapid and seemingly unstoppable changes occurring in the higher education climate as a result of global reform and with it the effect that change is having within the realm of academic leadership. Of some interest particularly is the effect that change is having at the level of middle-level academics in leadership roles. Many universities throughout Australia have established various 'leadership capability frameworks' to meet the need of leadership and management development. However, consideration needs to be given to how well these programs prepare middle-level academics for their leadership roles.